Analisis Keberlanjutan Bisnis Kebun Binatang Medan Ditinjau Dari Prespektif Ekonomi Islam - Azzahra, Alivia; Arif, Muhammad; Harianto, Budi (Universitas Hamzanwadi, 2024)
This research aims to find out and examine how sustainable the Medan Zoo business is from an Islamic Economic Perspective. Running a sustainable economy can be said to be the same as upholding Islamic law. Medan Zoo is one of the oldest tourist attractions in Indonesia which has a diversity of animals and is an educational place. However, in the past 2 years there have been various problems, one of which is that several rare animals have died. This research uses qualitative research methods with an observation and literature study approach. The results of this research show that the Medan city government has not been optimal in its efforts to sustain the Medan Zoo garden business from an Islamic economic perspective. This can be seen from humans as zoo managers who are less than optimal in caring for the animals in the Medan Zoo because salaries are not given. , The environment is damaged due to the lack of more attention from the city government as the person responsible for the Medan Zoo, and a decrease in profits caused by no change in quality both in terms of environment and facilities as well as competition with other tourist attractions